Engineering mathematics : a foundation for electronic, electrical, communications, and systems engineers - Croft, Tony, 1957-; Davison, Robert; Hargreaves, Martin (Harlow, England ; New York : Prentice Hall, 2001)
This text presents the "how" & "why" of engineering mathematics, carefully balancing techniques with conceptual understanding. The objective throughout is to give students the confidence & skills to solve both simple & complex engineering.
16.Further Topics In Integration. 17.Numerical Integration. 18.Taylor Polynomials, Taylor Series And Maclaurin Series. 19.Ordinary Differential Equations I. 20.Ordinary Differential Equations II. 21.The Laplace Transform. 22.Difference Equations And The Z Transform. 23.Fourier Series. 24.The Fourier Transform. 25.Functions Of Several Variables. 26.Vector Calculus. 27.Line Integrals And Multiple Integrals. 28.Probability. 29.Statistics And Probability Distributions. Appendix. I.Appendix. II.Appendix. III.Appendix. IV.Key Results.
Includes index.
1
Keywords: Engineering mathematics; Electrical engineering -- Mathematics; Electronics -- Mathematics